Compact gain-saturated x-ray lasers down to 6.85 nm and amplification down to 5.85 nm - Rockwood, Alex, author; Wang, Yong, author; Wang, Shoujun, author; Berrill, Mark, author; Shlyaptsev, Vyacheslav N., author; Rocca, Jorge J., author; Optical Society of America, publisher (Colorado State University. Libraries, 2018)
Plasma-based x-ray lasers allow single-shot nano-scale imaging and other experiments requiring a large number of photons per pulse to be conducted in compact facilities. However, compact repetitively fired gain-saturated x-ray lasers have been limited to wavelengths above λ = 8.85 nm. Here we extend their range to λ = 6.85 nm by transient traveling wave excitation of Ni-like Gd ions in a plasma created with an optimized pre-pulse followed by rapid heating with an intense sub-picosecond pump pulse. Isoelectronic scaling also produced strong lasing at 6.67 nm and 6.11 nm in Ni-like Tb and amplification at 6.41 nm and 5.85 nm in Ni-like Dy. This scaling to shorter wavelengths was obtained by progressively increasing the pump pulse grazing incidence angle to access increased plasma densities. We experimentally demonstrate that the optimum grazing incidence angle increases linearly with atomic number from 17 deg for Z = 42 (Mo) to 43 deg for Z = 66 (Dy). The results will enable applications of sub-7 nm lasers at compact facilities.
Keywords: x-rays; coherence; amplification; recovery; gain; amplifiers; molybdenum; lasers; lasers, optics, and electronics (so); photonics (general) (ea); optics (ah)